MECHANICAL MODELLING OF OBLIQUE CONVERGENCE IN THE ZAGROS, IRAN - Vernant P.; Chéry J. (My University, 2006)
Recent GPS surveys indicate that the Zagros kinematics corresponds to an oblique convergence between a rigid central Iranian plateau and the Arabian plate at ~7 mm yr-1 at the longitude of the Persian Gulf. Convergence is almost frontal in the SE Zagros and oblique (45°) in the NW part of the range. It has been proposed that internal deformation of the NW Zagros occurs in a partitioned mode. In such a view, the Main Recent Fault (MRF) bordering the Iranian plateau accommodates all the tangential motion, while shortening happens by pure thrusting within the fold and thrust belt as suggested by the focal mechanisms within the range. We use a 2.5-D mechanical finite element model of the Zagros to understand the influence on the Zagros deformation of (1) the obliquity of convergence, (2) the rheological layering of the lithosphere (strong upper crust, weak lower crust, strong or weak uppermost mantle) and (3) a possible weakness of the MRF. Surprisingly, a fully partitioned mode occurs only when the collision is very oblique. In the case of the NW Zagros, we find that the MRF can accommodate only ~25 per cent of the whole tangential motion. As the GPS inferred range parallel motion across the NW Zagros is ~5 mm yr-1, the present day slip rate of this fault could be as low as 1.2 mm yr-1. In agreement with the observed strain in SE Zagros, our model predicts that no strike-slip activity takes place on a vertical fault when the direction of convergence is more frontal. We discuss the implications of our model on the seismicity and kinematics of oblique collision zones by comparing our results with the available data in the Zagros and other oblique convergence domains. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: FAULT MODEL; FINITE-ELEMENT METHODS; LITHOSPHERIC DEFORMATION; OROGENY; RHEOLOGY